Effect of UV irradiation and physical aging on O2 and N2 transport properties of thin glassy poly(arylene ether ketone) copolymer films based on tetramethyl bisphenol A and 4, 4′-difluorobenzophenone. (22nd March 2016) - Liu, Qiang; Shaver, Andrew T.; Chen, Yu; Miller, Gregory; Paul, Donald R.; Riffle, J.S.; McGrath, James E.; Freeman, Benny D.
Abstract: Modification of membranes to improve gas separation properties has been of considerable interest. Crosslinking is one route to modify membranes, but such studies need to be performed on thin membranes to quantify the impact of such modifications at thicknesses relevant to industrial membranes. In this study, the influences of UV irradiation and physical aging on O2 and N2 gas permeation properties of thin (∼150 nm) glassy, amorphous poly(arylene ether ketone) (PAEK) copolymer films at 35 °C and 2 atm were investigated. Thin PAEK copolymer films, prepared from tetramethyl bisphenol A (TMBPA) and 4, 4′-difluorobenzophenone (DFBP), were UV irradiated on both sides in air or N2 at 254 nm or 365 nm, which induced crosslinking and, in some cases, photooxidation. Gas permeability decreased and O2 /N2 selectivity increased as UV irradiation and aging time increased. At 254 nm, samples irradiated in air have lower permeability coefficients and higher selectivities than samples irradiated in N2, which was ascribed to additional decreases in free volume due to photooxidation in samples irradiated in air. Additionally, samples irradiated in air at 254 nm exhibit less physical aging than uncrosslinked and samples irradiated in N2 at 254 nm, possibly due to interactions among photooxidative polar products that may restrict polymer chain mobility, thereby lowering the aging rate. The influence of water vapor on physical aging of samples irradiated in air was examined. Finally, irradiation at 254 nm leads to more extensive crosslinking and/or photooxidation than irradiation at 365 nm, possibly due to greater UV absorption by the polymer and the higher probability of radical formation at the lower wavelength. Graphical abstract: Highlights: Submicron poly(arelene ether ketone) copolymer films were UV irradiated. Permeability increases and selectivity decreases with increasing UV irradiation time and aging time. Gas permeation properties depend on UV irradiation environment. Aging environment influences polymer aging behavior.